Pembelajaran Snowball Throwing dan Motivasi Belajar terhadap Hasil Belajar IPS - Yuli Astutik (Jurnal Penelitian dan Pendidikan IPS, 2020)
Abstract The purpose of this study was to determine: (1) the effect of snowball throwing learning and learning motivation on the learning outcomes of social studies subjects of high class students, (2) the effect of snowball throwing learning with the learning outcomes of social studies subjects of high class students, and (3) the effect of learning motivation with the learning outcomes of Social Studies students of High Class SDN Sedarum I Nguling Pasuruan. This research is quantitative research. The study population was students of SDN Sedarum I Nguling District, Pasuruan Regency, a total of 273 students. The research sample was 138 High Class students with a total sample technique. Data collection using instruments. As for the learning outcomes of social studies subjects use tests. The results showed that: (1) there was a significant relationship between snowball throwing learning and learning motivation towards the learning outcomes of Social Studies students in High Classes, (2) there was a significant relationship between snowball throwing learning with High Class students' learning motivation, and (3 ) there is a significant relationship between learning motivation with the learning outcomes of social studies subjects of High Class students at SDN Sedarum I, Nguling Pasuruan.